2009
DOI: 10.4102/sajip.v35i1.833
|View full text |Cite
|
Sign up to set email alerts
|

Psychological career resources as predictors of working adults’ career anchors: An exploratory study

Abstract: This study explored the relationship between the psychological career resources and career anchors of a sample of 2 997 working adults at predominantly managerial and supervisory levels in the service industry. The Psychological Career Resources Inventory and the Career Orientations Inventory were applied. Stepwise regression analyses indicated dimensions of psychological career resources as signifi cant predictors of participants' career anchors. The fi ndings add valuable new knowledge that can be used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 34 publications
6
40
0
1
Order By: Relevance
“…In addition, the significant relationship observed between occupation performed, calling work orientation and the work-family balance values, suggests that participants who value conciliation between all that, deserve to improve their employability characteristics and abilities, not forgetting their highly enthusiastic contribution to the organization. These findings are in agreement with those of Coetzee and Esterhuizen (2010). The authors found that if people were clear about their career goals, they would be more optimistic and emotionally balanced.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, the significant relationship observed between occupation performed, calling work orientation and the work-family balance values, suggests that participants who value conciliation between all that, deserve to improve their employability characteristics and abilities, not forgetting their highly enthusiastic contribution to the organization. These findings are in agreement with those of Coetzee and Esterhuizen (2010). The authors found that if people were clear about their career goals, they would be more optimistic and emotionally balanced.…”
Section: Discussionsupporting
confidence: 83%
“…As Rego & Cunha (2005) said, "if managers aim to build healthy and effective organizations, they may want need to pay attention to a number of aspects: (a) their ethical, honest, respectful and trustful way of acting; (b) the opportunities for learning and personal development that they provide to employees; (c) the degree to which they take employees as people in search of meaningful work and a positive sense for life; (d) the honesty and frankness they place in communicating with subordinates; (e) the ways they allow their subordinates to strike a balance between work and family; (f) the ways they promote a spirit of camaraderie and teamwork; (g) the fairness that they express in their decisions, namely those involving promotions and rewards." Coetzee and Bergh (2009) The main limitation is that the work orientations results, mostly the career dimension ones,…”
Section: Resultsmentioning
confidence: 99%
“…South African studies that explore the concept of career success are however rather limited, especially in terms of capturing subjective career success of senior managers who are generally perceived to have successful careers based on their income, status and occupational level (Ng et al, 2005). The majority of SA studies that have been conducted have been quantitative and focused mainly on the following: psychological factors in career situations as antecedents of women academics' success in their careers in South Africa (Riordan, 2007), career success of women academics in South Africa (Riordan & Louw-Potgieter, 2011), psychological career resources as predictors of working adults' career anchors (Coetzee & Bergh, 2009), and the influence of career orientations on subjective work experiences . In a qualitative study on career success done by Rowe and Crafford.…”
Section: Overview Of Literature On Career Success In South Africamentioning
confidence: 99%
“…If organisations endeavour to retain their valuable and key senior managers, they need to provide them with appropriate incentives and career paths that are in line with the career values, expectations and aspirations that underpin the career orientations of these employees (Coetzee & Bergh, 2009;Järlström, 2000;Schein, 1996;Suutari & Taka, 2004). Should organisations fail to create conditions where the work environment and the employee's inner subjective career orientation are compatible, the result may well be anxiety, stress, unhappiness, job and career dissatisfaction, and increased turnover (Coetzee & Berg., 2009;Feldman & Bolino, 1996;Jiang & Klein, 2000;Jiang, Klein & Balloun, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, interest in the subjective aspects of career success and satisfaction has gained greater salience in contemporary career research. This can be ascribed to the more turbulent career context resulting in careers being less ordered and predictable (Arnold and Cohen 2008;Arthur, Khapova and Wilderom 2005;Coetzee and Bergh 2009;Hall andChandler 2005 Kidd 2008;Sinclair 2009). Contemporary measures of people's subjective experiences of their careers and working lives tend to focus on the career self-concept or identity, the internal career orientation and the core self-evaluations relating to people's psychological career resources or career meta-competencies (Coetzee 2008, Coetzee andSchreuder 2009b;Fugate, Kinicki and Ashforth 2004;Kanye and Crous 2007;Kuijpers and Scheerens 2006;Sinclair 2009;Van Dam 2004;Van der Heijde and Van der Heijden 2006).…”
mentioning
confidence: 99%